Verbal Encouragement and Between-Day Reliability During High-Intensity Functional Strength and Endurance Performance Testing - Engel, Florian A.; Faude, Oliver; Kölling, Sarah; Kellmann, Michael; Donath, Lars (Frontiers in Physiology, 2019)
As verbal encouragement is used in high intensity functional exercise testing (HIFT), this randomized controlled crossover study aimed at investigating whether verbal encouragement (VE) affects high intensity functional strength and endurance performance testing, framed by a typical CrossFit setting. We further examined between-day variability of CrossFit-specific strength and endurance performance testing with and without VE. Nineteen experienced CrossFit-athletes (7 females and 12 males, age: 23.7 ± 4.3 years) performed a standardized and typical CrossFit one repetition maximum squat test and a typical 12-minute CrossFit endurance workout (as much repetitions as possible, AMRAP) on four different days over a 2-week period. Athletes randomly performed each test twice, either with VE or without (CON), with a minimum of 72 hours rest between tests. Very good to excellent relative between-day reliability with slightly better values for strength testing (ICC: 0.99; CV: 3.5%–4.1%) compared to endurance testing (ICC 0.87–0.95; CV: 3.9–7.3%) was observed. Interestingly, VE led to higher reliability during endurance testing. Mean squat strength depicted higher strength values with VE (107 ± 33 kg) compared to CON (105 ± 33 kg; p = 0.009, Cohen’s d: 0.06). AMRAP in the endurance test showed negligible differences between VE (182 ± 33 AMRAP) and CON (181 ± 35 AMRAP; p = 0.71, Cohen’s d: 0.03). In conclusion, the effects of VE do not notably exceed day-to-day variability during CrossFit-specific strength and endurance performance testing but testing under VE condition seems to be slightly more reliable, particularly during endurance testing.